Poverty and Economic Growth: The Socioeconomic Determinants of Stunting Prevalence in Indonesia - Sayekti Suindyah Dwiningwarni; Syamsiyah Yuli Dwi Andari; Habibi Ainul Yaqin (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This study provides recent provincial evidence from Indonesia (2010–2024) on the nexus between poverty, economic growth, and stunting. Research Objectives: This study aims to investigate the effects of poverty and economic growth on stunting prevalence in Indonesia, using parental education level and the open unemployment rate as proxies. Research Methods: This study employs path analysis using a natural-log approach, analyzing data from 2000 to 2023. Key variables include socioeconomic determinants and stunting prevalence. Empirical Results: The findings of this study include: poverty has a negative and significant effect on parental education and open unemployment, while economic growth has no significant effect on parental education and open unemployment; poverty affects the prevalence of stunting through parental education and open unemployment, while economic growth does not affect the prevalence of stunting through parental education and open unemployment. Implications: The findings suggest that reducing stunting requires inclusive economic growth and effective poverty alleviation. Therefore, policies should focus on strengthening social protection and improving access to nutrition and health services. JEL Classification: I21, E24, C32, I10, I31 How to Cite:Dwiningwarni, S S., Andari, S. Y. D., & Yaqin, H. A. (2026). Poverty and Economic Growth: The Socioeconomic Determinants of Stunting Prevalence in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 15(2), 373-390. https://doi.org/10.15408/sjie.v15i2.50601.